2007
DOI: 10.1007/s00464-007-9501-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of preoperative rofecoxib, metoclopramide, dexamethasone, and ondansetron on postoperative pain and nausea in patients undergoing elective laparoscopic cholecystectomy

Abstract: The use of this preoperative regimen resulted in decreased LOS, maximum pain, and nausea ratings. Patients in the intervention group required less postoperative anti-emetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…All three studies showed decreased postoperative pain scores and a reduced requirement for postoperative opioid analgesia. Four trials 2,30–32 evaluated COX II inhibitors. All four trials showed a reduction in postoperative pain and two trials 30,31 reported increased patient satisfaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All three studies showed decreased postoperative pain scores and a reduced requirement for postoperative opioid analgesia. Four trials 2,30–32 evaluated COX II inhibitors. All four trials showed a reduction in postoperative pain and two trials 30,31 reported increased patient satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…Laparoscopic cholecystectomy (LC) is currently accepted as the reference standard for the management of symptomatic or complicated gallstone disease. There is now increasing evidence to support ambulatory LC as the standard of care as a result of its ability to improve patient recovery and significantly reduce hospital stay 1–4 . Laparoscopic cholecystectomy would appear to be an ideal operation for ambulatory surgery because it is of short duration, uses small incisions, carries a low rate of immediate complications and does not disrupt gastrointestinal homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…digestive tract and stimulates bowel movement. Furthermore, since metoclopramide enhances the esophageal sphincter resting pressure, it can limit reflux of the gastric contents to the esophagus through broadening the range of the esophageal contractions [6][7][8].…”
Section: Biomedical Research 2018; 29 (15): 3043-3046mentioning
confidence: 99%